The Dawn of the Porttinari Multigenre Treebank: Introducing its Journalistic Portion - Duran, Magali Sanches; Lopes, Lucelene; Nunes, Maria das Graças Volpe; Pardo, Thiago Alexandre Salgueiro (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2023: Anais do XIV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2023)
This paper introduces the journalistic portion of the Porttinari treebank, which aims to be a multigenre NLP resource for Brazilian Portuguese. We report the construction of the treebank, in particular, the human-revised portion with 8,418 sentences, whose annotation process lasted almost three years and involved more than a dozen trained annotators. The full treebank offers to the Portuguese-speaking NLP community nearly 4 million sentences annotated according to the Universal Dependencies framework.